The impact of perceived internal CSR through leisure sport-based initiatives on employees’ organizational identification, job satisfaction, job engagement and turnover intentions, and the mediating role of organizational identification: proposition of a research model - ABOUKINANE , Mohamed Amine; BIAZ , Sanae; EL JOUD , Salma; OUADDAR , Widad; NAMYECH , Asma; HOSNI , Yassine (Revue Internationale des Sciences de Gestion, 2025)
By reviewing the existent literature and mobilizing the relevant theories, the current work aims at proposing a research model concerning the impact of perceived internal corporate social responsibility (PICSR) through leisure sport-based initiatives on behavioral and attitudinal employees’ outcomes such as organizational identification, job satisfaction, job engagement, and turnover intention. We will also highlight the potential mediating role that the organizational identification construct could play between perceived internal corporate social responsibility through leisure sport-based initiatives and employees’ job satisfaction, job engagement, and turnover intention. The results of this theoretical research will be further supported empirically by adopting a quantitative approach through the administration of a questionnaire among employees of companies that have been labeled “Sport Company” due to the fact that those companies have already started implementing wellness programs through the initiation of leisure sport-based initiatives to promote physical activity among their employees.